Prevalence of congenitally missing upper lateral incisors in an orthodontic adolescent population - C Swarnalatha (Journal of Orthodontic Science, 2020)
OBJECTIVE: To determine the frequency of congenitally missing maxillary lateral incisors (LIs) and to find out its variability in relation to gender. MATERIALS AND METHODS: A retrospective study was carried out between January 2017 and December 2017. Orthopantomographs (OPGs) and lateral cephalographs record search of all orthodontic adolescent patients aged 12 to 18 years were taken from the archival records of the department. Orthopantomographs helped to diagnose the presence of unilateral/bilateral maxillary lateral incisors while the ANB angle was calculated from the lateral cephalographs to divide the subjects into various skeletal malocclusions. STATISTICAL ANALYSIS USED: The statistical analysis was done using the Statistical Package for Social Sciences (SPSS version 17.0). The frequencies were compared with the help of the Chi-square test. P<0.05 was considered statistically significant. RESULTS: The frequency of missing upper laterals among the male patients was 0.9%, however, 2.8% of the female patients were having missing maxillary lateral incisors. Based on gender, 62.16% had a bilateral expression of missing upper laterals, 16.21% had left unilateral expression, and 21.62% had right unilateral expression. Furthermore, skeletal class I malocclusion had a prevalence of 54.16% of bilateral missing lateral incisors in upper arch as compared to 40% of left unilateral expression and 37.5% of right unilateral expression whereas in skeletal class II malocclusion, the prevalence of right unilateral expression was 37.5% as compared to bilateral expression which was 33.33%. The left unilateral expression in skeletal class II malocclusion was found to be only 20%. The highest prevalence of missing laterals in skeletal class III malocclusion was left unilateral expression which was around 40%. The prevalence of right unilateral expression was 25% whereas the bilateral absence of upper laterals in skeletal class III malocclusion was 12.5%. CONCLUSION: The prevalence rate for congenitally missing upper lateral incisors in the orthodontic adolescent population aged 12 to 18 years was found to be 3.77% in the present study while females were found to have a greater percentage of agenesis of the upper lateral incisors (2.8%) as compared to the males (0.9%).